Bhabinkamtibmas Polmas Activities Model in Preventing Radicalism in Bandung Police Department - Putri Yolanda Permata Sari (Advances in Police Science Research Journal, 2021)
This research is motivated because the impact of the spread of radicalism in Bandung Regency is increasing seeing the number of cases and findings that exist in Bandung Regency. So that it takes the participation of members of the National Police to participate in the prevention of radicalism by referring to the Regulation of the National Police Chief Number 3 of 2015. Prevention of radicalism is carried out through Bhabinkamtibmas activities and accompanied by inhibiting and supporting factors. The theories used to analyze these problems are communication theory and Force Field Analysis theory. Meanwhile, the concepts used in this study are the concept of Bhabinkamtibmas, the concept of radicalism, and the concept of Community Policing. To analyze the approach between Bhabinkamtibmas and society, the writer uses the application of communication theory. Meanwhile, to analyze the relationship with the factors that influence the implementation of Bhabinkamtibmas activities, the authors use Force Field Analysis theory as a tool of analysis. The research method uses a qualitative approach whose results are reinforced by the presence of findings, observations, document studies, and interviews with information sources. The techniques used for data analysis include data reduction and formulating working hypotheses by formulating a proportional question. The results of the study found that the implementation of Bhabinkamtibmas activities in order to prevent radicalism has not run optimally because of several factors that influence, such as there are still Bhabinkamtibmas who are involved in guarding the police and police. In addition, the supply of infrastructure is also inadequate. From the findings of research in the field, the authors suggest to the Bandung Police Satbinmas to further improve the quality of human resources and complete infrastructure that can support the implementation of Bhabinkamtibmas activities in preventing radicalism at the Bandung Police.